SOSIALISASI MAKANAN BERGIZI MELALUI PROGRAM GIZILAND UNTUK PENCEGAHAN STUNTING DI SD NEGERI BUTUH, TEMANGGUNG - Wijayanto, Sahrul Lukman; Wibawa, Wildan Fatwa Satriya; Maulana, Roki Faris; Wicaksono, Ahmad Humam Bagus; Hartono, Budi (ICON Publisher, 2025)
Stunting remains a major challenge in improving human resource quality in Indonesia. Temanggung Regency has been recorded as the region with the highest stunting prevalence in Central Java Province, reaching 27.3% in 2024. In response to this condition, Universitas Tidar’s community service students implemented a nutrition education program for elementary school students through an initiative called Giziland, conducted at SD Negeri Butuh. This activity aimed to enhance children’s understanding of nutritious food as an early prevention effort against stunting. The program consisted of two stages: an initial survey and an educational socialization session. The activities were tailored to the students’ grade levels: lower-grade students participated in coloring fruits and vegetables and matching food pictures with their nutritional content, while upper-grade students competed in a health quiz on balanced nutrition. The program successfully increased students’ knowledge about healthy foods and fostered greater awareness of adopting healthy eating habits. This initiative demonstrates that creative and enjoyable nutrition education can serve as a strategic step in sustainably reducing stunting rates.